Poetic Metaphors Related to Birds: A Conceptual Blending in Puisi-Puisi Cinta, WS. Rendra - Jaganegara, Haidar (Jurnal Bahasa Asing, 2024)
Metaphors are commonly used to vividly convey deeply abstract human emotions. This is because human emotions are indeed an abstract – conceptual. In the poem of Puisi-Puisi Cinta, the poet employs a great deal of emotional poetic metaphors relating to birds in order to communicate the variety of feelings that are experienced by the characters, such as features, roles, and visual aspects. This paper aims to study the emotional poetic metaphors related to birds in Puisi-Puisi Cinta using conceptual blending theory. The research data in the study consists the poetic metaphors related to Birds in Puisi – Pusi Cinta by WS Rendra. The data are conducted qualitatively using the blending theory. The blending theory’s G.Fauconnier and M.Turner (2002) came to the conclusion that metaphorizing is not limited by the projection from “the source domain” to “the target domain”, but includes complex dynamic integration processes, creating new blended mental spaces, which are able to create the meaning structure. The findings reveal that these vivid poetic metaphors in Puisi-Puisi Cinta by W.S Rendra are substantial through the use of imagery depicting aspects of the birds' appearances and its features to human beings. The metaphorical process, which projects from the birds to human beings, can be seen as a process of conceptual blending. In addition, each and every poetic metaphor related to birds of the poem has its characteristics in a certain cognitive model.